Omonimie sistematiche e assi del paradigma nel verbo italoromanzo centromeridionale (Atti del Sodalizio Glottologico Milanese, 2018)
The present paper aims to provide a brief survey of two kinds of morphological change shown by the diachronic development of the Central-Southern Italo-Romance verbal system. On the one hand, a series of systematic homophonies between inflected forms arises for reasons not related to sound changes: such syncretisms typically involve tense(-aspect)/mood values and affect paradigm cells with low usage frequency (especially 1st and 2nd person plural cells). On the other hand, a second series of events conspires to enhance formal dissimilarities related to distinctions of person, thus reducing the amount of person syncretism instances created by final vowel reduction. The observed phenomena seem to corroborate the idea that paradigm cells with low usage frequency are more prone to synchronic syncretism, but also show that in a particular system different tendencies with respect to syncretism-tolerance or avoidance can be associated with different paradigm dimensions. KEYWORDS: morphological change, Central-Southern Italo-Romance, verbal paradigms, homophony, syncretism